2004
DOI: 10.1007/s00122-004-1644-6
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana chromosome III restores fertility in a cytoplasmic male-sterile Brassica napus line with A. thaliana mitochondrial DNA

Abstract: Somatic Brassica napus (+) Arabidopsis thaliana hybrids with a cytoplasmic male sterility (CMS)-inducing cytoplasm were screened for fertility-restored plants. One line was selected and recurrently backcrossed with the maintainer line, B. napus, resulting in fertile/sterile segregating populations. Restriction fragment length polymorphism mapping showed the co-segregation of A. thaliana chromosome (chr) III markers with the fertility trait. As it was not possible to stabilise the fertility trait via selfings, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…This further testified that the fertility restoration gene(s) of alloplasmic CMS lines generally existed in nuclear genome of cytoplasm donor species. The restoration gene of a B. napus CMS line with rearranged A. thaliana mtDNA was located on chromosome III of A. thaliana (Leino et al, 2004). The restorer line for Nsa CMS of B. napus developed by the somatic hybridization with Sinapis arvensis was one disomic addition line with the restoration gene on the alien chromosome (Wei et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This further testified that the fertility restoration gene(s) of alloplasmic CMS lines generally existed in nuclear genome of cytoplasm donor species. The restoration gene of a B. napus CMS line with rearranged A. thaliana mtDNA was located on chromosome III of A. thaliana (Leino et al, 2004). The restorer line for Nsa CMS of B. napus developed by the somatic hybridization with Sinapis arvensis was one disomic addition line with the restoration gene on the alien chromosome (Wei et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the cybrids between tobacco and Hyoscyamus niger showed late germination of seeds, dramatic decrease in chlorophyll in vivo and pigment deficiency in cotyledons in vitro owing to nucleo-cytoplasmic incompatibilities (Zubko et al, 2001). In addition, alloplasmic incompatibility between nucleus and mitochondria was reported to be responsible for CMS in somatic hybrids between A. thaliana and B. napus and their progenies (Leino et al, 2004).…”
Section: Interactions Between Nuclear and Cytoplasmic Genomesmentioning
confidence: 96%
“…Besides, CMS present in some species with reproductive defects cannot be transferred by traditional way. To date successful CMS transfer via protoplast fusion has been accomplished in several combinations, such as sunflower and chicory (Rambaud et al, 1993;Varotto et al, 2001), A. thaliana and B. napus (Forsberg et al, 1998a;Leino et al, 2003Leino et al, , 2004, R. sativus and B. oleracea (Kameya et al, 1989;Kanno et al, 1997), tobacco and Petunia hybrida (Dragoeva et al, 1999), B. juncea + Moricandia arvensis . In addition intergeneric transfer of CMS has been accomplished between R. sativus and B. napus via cytoplast-protoplast fusion (Sakai and Imamura, 1990).…”
Section: Transfer Of Resistance To Biotic and Abiotic Stressesmentioning
confidence: 98%
“…A recombined mitochondrial genome was found in B. napus CMS lines derived from somatic hybridization with A. thaliana (Carlsson et al 2007, Leino et al 2003, 2004, Teixeira et al 2005). The association of fertility restoration with markers on chromosome 3 of A. thaliana suggested that the male sterility genes are also derived from A. thaliana (Leino et al 2004). …”
Section: Origins Of Cms and Male Sterility-inducing Mitochondrial Genesmentioning
confidence: 99%